2019
DOI: 10.1089/bfm.2019.0202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Skin-to-Skin Care During Cesareans: A Quasiexperimental Feasibility/Pilot Study

Abstract: Introduction: Our aim was to describe feasibility and outcomes of skin-to-skin care (SSC) that began during cesarean surgery and continued, uninterrupted, for about 5 hours. We described maternal/newborn measures of physiologic stability and stress; maternal measures of comfort; maternal satisfaction with surgery and SSC; and exclusive breast milk feeding at discharge. Materials and Methods: We used a quasiexperimental, time-interrupted design and randomly assigned women to receive SSC that began during surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…Pain perception following Caesarean section was lower and maternal satisfaction was higher in the early SSC group than the control group in another study by Sundin and Mazak. 36 Crenshaw et al 38 also demonstrated higher maternal satisfaction and lower salivary cortisol when they compared early and late SSC groups.…”
Section: Effect Of Early Ssc On Parent-infant Interactionmentioning
confidence: 95%
“…Pain perception following Caesarean section was lower and maternal satisfaction was higher in the early SSC group than the control group in another study by Sundin and Mazak. 36 Crenshaw et al 38 also demonstrated higher maternal satisfaction and lower salivary cortisol when they compared early and late SSC groups.…”
Section: Effect Of Early Ssc On Parent-infant Interactionmentioning
confidence: 95%
“…Delaying or withholding immediate and uninterrupted SSC during a medically uncomplicated caesarean is usually not necessary (Crenshaw et al, 2019) and may be harmful (Cs asz ar-Nagy & B okkon, 2018;World Health Organization [WHO] & UNICEF, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Delaying or withholding immediate and uninterrupted SSC during a medically uncomplicated caesarean is usually not necessary (Crenshaw et al, 2019) and may be harmful (Császár‐Nagy & Bókkon, 2018; World Health Organization [WHO] & UNICEF, 2018). Given the global rate of caesarean birth (Boatin et al, 2018; Boerma et al, 2018; Visser et al, 2018), at least one‐third of women and their newborns may not have access to this evidence‐based practice that significantly improves breastfeeding outcomes and promotes optimal health for women and children (Császár‐Nagy & Bókkon, 2018; WHO & UNICEF, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementing STS contact in the operating room promoted family centered care, improved the mother's satisfaction and confidence (Crenshaw et al, 2019), provided a more natural experience and sense of control (Bertrand & Adams, 2020;Frederick et al, 2016Frederick et al, , 2020, and facilitated bonding (Bertrand & Adams, 2020) and attachment (Hubbard & Gattman, 2017;Neczypor & Holley 2017). Contraindications may include maternal or neonatal instability or conditions not supportive of interaction (i.e., vomiting, use of general anesthesia; Frederick et al, 2020).…”
mentioning
confidence: 99%